Review: Julia Rensing, Lorena Rizzo and Wanda Rutishauser, (eds.), Sites of Contestation. Encounters with the Ernst and Ruth Dammann Collection in the Archives of the Basler Africa Biblio-graphien, Basel, Basler Afrika Biblio-graphien, 2021 (Journal of Namibian Studies : History Politics Culture, 2022)
Review of: Julia Rensing, Lorena Rizzo and Wanda Rutishauser, (eds.), Sites of Contestation. Encounters with the Ernst and Ruth Dammann Collection in the Archives of the Basler Africa Bibliographien, Basel, Basler Afrika Bibliographien, 2021.